Can heart rate variability biofeedback improve athletic performance? A systematic review - Pagaduan, J. C.; Chen, Y. S.; Fell, J. W.; Wu, S. S. X. (Journal of Human Kinetics, 2020)
This systematic review was conducted to evaluate the effect of heart rate variability biofeedback (HRV BFB) on performance of athletes. Six electronic databases (Springerlink, SportDiscus, Web of Science, PROQUEST Academic Research Library, Google Scholar, and ScienceDirect) and article references were searched. Eligibility criteria were: 1. experimental studies involving athletes randomly allocated among groups (randomized control trial); 2. availability of HRV BFB as a treatment compared to a control condition (CON) that involves regular sport/dance training, a placebo (PLA) or other methods of BFB; 3. performance-related variables such as a dependent index; and, 4. peer-reviewed articles written in English. Out of 660 articles, six studies were included in the systematic review which involved 187 athletes (females: n = 89; males n = 98). Six studies compared HRV BFB with a CON, three studies compared HRV BFB with a PLA, and two studies differentiated HRV BFB with other methods of BFB. Findings support HRV BFB as a potential intervention to improve fine and gross motor function in athletes.